Proliferative response and oncogene expression induced by epidermal growth factor in EL2 rat fibroblasts. - Liboi, E (1986)
Extensive evidence supports a two-step model for the control of fibroblast growth, which includes first the action of a competence factor (e.g., platelet-derived growth factor) followed by the stimulus of a progression factor (e.g., epidermal growth factor [EGF]). We investigated whether this model may be applied to the euploid EL2 fibroblast line recently isolated from rat embryos (E. Liboi, M. Caruso, and C. Basilico, Mol. Cell. Biol. 4:2925-2928, 1984). Our results clearly show that EGF alone leads EL2 cells to proliferate in serum-free conditions at a rate corresponding to 50 to 60% of that observed in the presence of 10% calf serum. It is of interest that, when resting EL2 cells were exposed to EGF, transcription of both c-myc and c-fos was markedly induced. Altogether, these observations suggest that, in contrast with the model of fibroblast growth mentioned above, EL2 cells require the presence of a single growth factor (EGF) for induction of DNA synthesis, and the expression of myc and fos proto-oncogenes may represent an obligatory step in the pathway of commitment of EL2 cells to proliferation. In addition, we showed that EGF may induce EL2 cells to acquire some properties of transformed cells, such as growth in agar and loss of contact inhibition. This suggests that the particular response to EGF of the EL2 line may be strictly connected with the expression of a transformed phenotype.